Improved performance and air stability of planar perovskite solar cells via interfacial engineering using a fullerene amine interlayer. (October 2016) - Xie, Jiangsheng; Yu, Xuegong; Sun, Xuan; Huang, Jiabin; Zhang, Yunhai; Lei, Ming; Huang, Kun; Xu, Dikai; Tang, Zeguo; Cui, Can; Yang, Deren
Abstract: The recent rapid rise in power conversion efficiencies (PCEs) of perovskite solar cells (PSCs) has attracted worldwide extensive attention. However, the PSC applications are limited by their poor stability due to perovskite degradation in moisture. We used a fullerene amine interlayer in planar PSCs to reduce the interface barrier between ETL and metal electrode and also resist the moisture. The utilization of fullerene amine interlayer allowed for the enhancement of PSCs' performance, showing a highest power conversion efficiency (PCE)>17.2% with negligible hysteresis. More importantly, the air stability of PSCs with fullerene amine was improved: the unpackaged devices stored in air can keep their high performance with no obvious PCE loss in 10% humidity and >90% of the initial PCE in 45% humidity after 20 days. Graphical abstract: Improved performance and air stability of planar perovskite solar cells via interfacial engineering using a fullerene amine interlayer. Highlights: A highest PCE>17.2% has been achieved for the PSCs with PCBDAN. The devices with PCBDAN show higher performance. The improved stability of PSCs is related to the hydrophobic PCBDAN. PCBDAN can be used in the fabrication of high efficient and stable PSCs.